Manajemen Kinerja Pembangunan Kota Palembang: Analisis Komprehensif pada Aspek Infrastruktur, Lingkungan, dan Pelayanan Publik - Lies Nur Intan; Endy Agustian (Journal Of Plano Studies, 2026)
Palembang City, as the center of economic growth in South Sumatra Province, continues to face development challenges due to increasing urbanization, which has raised demands for infrastructure, environmental management, and public services. This study aims to comprehensively analyze the development performance management of Palembang City across three dimensions: infrastructure, environment, and public services. The study employs a mixed methods approach integrating qualitative and quantitative approaches, utilizing secondary data from planning documents, government performance reports, regulations, statistical data, and relevant literature, as well as primary data from a survey of 100 respondents selected through accidental sampling. The findings indicate that Palembang City’s development still faces significant challenges: (1) in infrastructure, suboptimal road network quality, public transport integration, water supply distribution, solid waste management, and drainage capacity; (2) in the environment, persistent air and water pollution, and inadequate waste management; and (3) in public services, the overall maturity level is categorized as moderate (66.46%), with conventional government services scoring 62.2%, digital services 70.9%, and community participation 66%. Therefore, strengthening development governance through cross-sectoral synergy, optimized use of information technology and geospatial data, and evidence-based policymaking is essential to support effective, inclusive, and sustainable development in Palembang City.